PENGEMBANGAN MANAJEMEN BERBASIS MADRASAH - Abdullah Abdullah (Nurul Jadid University, 2015)
Law No. 20 of 2003 on National Education System which mandates that the provision of education conducted by the school-based management principles / madrasah is evidence of seriousness of the government in addressing the aspirations of the people associated with the increased demands of the quality of education. In order to answer the challenges in the field of education and the expectations of society in the form of guidance to improve education quality, school-based management / madrasah (MBS / MBM) is an absolute thing that must be addressed and implemented, because theoretically MBS / MBM no longer make the government as the central authorities of education, but occurs disenteralisasi autonomy and education in Madrasah.